A transparent PEDOT:PSS/PVA-co-PE/epoxy thermoelectric composite device with excellent flexibility and environmental stability. (8th February 2022) - Zeng, Fanjia; Zhao, Xu; Luo, Mengying; Wang, Wen; Qing, Xing; Lu, Ying; Zhong, Weibing; Liu, Qiongzhen; Luo, Jie; Li, Mufang; Wang, Dong
Abstract: With the rapid development of thermoelectric (TE) generators, the TE device that is transparent, flexible, and can be used for a long time under high humidity and low/high temperature has aroused great interests. In this study, a new hydrophilic substrate of poly (vinyl alcohol-co-ethylene) (PVA-co-PE) nanofiber membrane was used to support the poly (3, 4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS), and then the PEDOT:PSS/PVA-co-PE composite was encapsulated by epoxy. Due to the size effect of nanofibers, the PVA-co-PE/epoxy composite area shows a good transmittance of 72% at a wavelength of 600 nm, while the area containing the PEDOT:PSS remains black. This kind of transparent packaging structure is more conducive to the application of TE device. Moreover, the special interpenetrating structure and hydrogen bonding between the three phases of PEDOT:PSS, PVA-co-PE NM and epoxy resin greatly enhance the interfacial adhesion of PEDOT:PSS/PVA-co-PE/epoxy composite. The morphology, mechanical properties, transmittance, TE performance, bending resistance and environmental stability of the transparent composite TE device were analyzed. The new composite structure proposed in this research gives the PEDOT:PSS/PVA-co-PE/epoxy TE device outstanding flexibility and environmental stability. The TE performance remains stable after 2000 cycles repeated bending and after placing one end of the TE device in hot steam and ice water. All the results demonstrate the potential application of the transparent composite TE device in the field of flexible electronic device packaging and applications. Graphical abstract: Image 1 Highlights: A transparent PEDOT:PSS/PVA-co-PE/epoxy TE device was prepared. The interpenetrating structures and hydrogen bonding enhanced the interfacial adhesion. The composite TE device shows outstanding flexibility to withstand repeated bending. The TE performance remains stable after in high humidity and high/low temperature environments.